A bibliography on Aboriginal and minority concerns: Identity, prejudice, marginalisation, and healing in relation to race, gender, sexuality, and the ecology of place - Bowers, R J (Australian Counselling Association, 2007)
This bibliography was initiated during late February 2007, following an invitation of the Mi’Kmaq Resource Centre at Cape Breton University in Nova Scotia, Canada, to donate my work to the archive.